Intelligent digital twins and the development and management of complex systems [version 1; peer review: 4 approved] - Michael Grieves (Digital Twin)
The interest in defining and implementing Digital Twins (DT) is at the forefront of today’s product organizations. The evolution of increasingly complex systems requires that their information be organized and managed via digital twins.  In addition, the development of Artificial Intelligence (AI) will result in an increasing degree of system complexity. These complex systems will exhibit true emergent behavior as AIs modify system aspects as the result of goal seeking and learning. DTs will need to increase in capability, becoming intelligent in their approach. This article presents a discussion on how these Intelligent Digital Twins (IDTs) will evolve and assist in developing and managing complex systems.